Pathways through rehabilitation for traumatic brain injury: preliminary results from an Irish study. (20th October 2021) - O'Donnell, K; Healy, A; Staines, A; Corrigan, C; Burke, T; McGettrick, G; Waldron, B
Abstract: Background: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. In Ireland, little data exists on the number of TBI survivors or the availability of brain injury rehabilitation services. To address this, we examined nationally representative data to estimate the number of moderate to severe TBI survivors and to learn of their rehabilitation experiences. Methods: A two-year mixed-methods, observational, cohort study was used to investigate the rehabilitation pathways of moderate to severe TBI survivors (N = 120). Participants were surveyed on two occasions six months apart using a range of standardised instruments (EQ-5D-3L, WHOQOL BREF and EBIQ). Preliminary findings from first surveys are reported. Results: Fifty percent of participants reported having received some rehabilitation during their initial hospitalization. Following discharge, inpatient rehabilitation was recommended in 55.8% of cases (N = 67); 62.5% (N = 75) in an outpatient setting and 52.1% (N = 62) in a specialised brain injury community-based setting. Rehabilitation was not recommended in 9.2% (N = 11) of cases. Univariant analyses showed statistically significant differences between the experiences of males (N = 87) and females (N = 33) in three main elements; Isolation: males (M), mean 1.88, SD .488, females (F) mean 1.64, SD .476, (p = .015); Communication: M mean 1.85, SD .565, F mean 1.57, SD .469 (p = .012); Cognitive difficulties: M mean 1.81, SD .456, F mean 1.59, SD .426 (p = .020). Discussion: Referrals to rehabilitation services varied substantially in this cohort of TBI survivors with evidence to suggest that, overall, males experience greater impacts on quality of life than do females. These findings support the need to, a) increase political priority and resource allocation for rehabilitation services for TBI survivors in Ireland and b) further study gender differences in TBI survivor outcome. Key messages: Survivors of moderate to severe brain injury in Ireland have very divergent, and often inadequate experiences of rehabilitation. There is some evidence that male survivors of moderate to severe traumatic brain injury face more challenges than do female survivors.